2019
DOI: 10.1111/ans.15628
|View full text |Cite
|
Sign up to set email alerts
|

Does emergency general surgery model affect staff satisfaction, training and working hours?

Abstract: Background Few studies have assessed the relationship between different emergency general surgery models and staff satisfaction, operative experience or working hours. The Royal Australasian College of Surgeons recommends maximum on‐call frequency of one‐in‐four for surgeons and registrars. Methods A cross‐sectional study was conducted of all medium‐ to major‐sized Australian public hospitals offering elective general surgery. At each site, an on‐call general surgery registrar and senior surgeon were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The framework conditions of the training cannot be easily transferred from elective surgery to emergency procedures. Emergency procedures often do not take place in the elective daily program, but are carried out at times of fewer resources [ 2 ], which narrows the corridor of trainees to the assistant on duty or specialist. Even with personal willingness, the Working Time Act also represents a restriction here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework conditions of the training cannot be easily transferred from elective surgery to emergency procedures. Emergency procedures often do not take place in the elective daily program, but are carried out at times of fewer resources [ 2 ], which narrows the corridor of trainees to the assistant on duty or specialist. Even with personal willingness, the Working Time Act also represents a restriction here.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of urgent or emergency surgical procedures, training assistants and trainers alike face various hurdles that need to be checked before the teaching assistance can possibly be implemented. This includes (1) the content knowledge of the training assistant about the case, (2) the practical skills to manage the emergency, and (3) the circumstances of the procedure in terms of complexity, resources, and patient endangerment.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of ASU studies have reported subjective outcomes, including the satisfaction of surgeons [10], trainees [11], emergency physicians [12] or even doctors’ approximations of patient satisfaction, estimated without patient input [12, 13]. None of these ASU studies have measured patient‐reported outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In the past 15 years or so, numerous benefits of the ACS model of care have been noted from improved outcomes, [11][12][13][14][15][16] increased efficiency, 11,15,17 and better job satisfaction. [18][19][20] One of the most important benefits of the ACS model is increased interest in the field. 21 If we accept Maier's premise that "applicant statistics for RRC-approved surgical critical care fellowships" can serve as surrogate marker for interest in acute care surgery, then we are on the right track.…”
mentioning
confidence: 99%
“…In the past 15 years or so, numerous benefits of the ACS model of care have been noted from improved outcomes, 11–16 increased efficiency, 11,15,17 and better job satisfaction 18–20 . One of the most important benefits of the ACS model is increased interest in the field 21 .…”
mentioning
confidence: 99%